2016
DOI: 10.1099/jmm.0.000336
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evaluation of a novel immunochromatographic assay for pharyngeal Mycoplasma pneumoniae ribosomal protein L7/L12 antigens

Abstract: Point-of-care testing for Mycoplasma pneumoniae infection may be ideal and useful because significant numbers of the cases will be seen as outpatients. Recently, a new immunochromatographic method (ICM) targeting M. pneumoniae ribosomal protein L7/L12 (RP-L7/L12) in pharyngeal swabs became available in Japan, although clinical data and basic information regarding efficacy and characterization of this ICM are limited. The present study examined the fate of M. pneumoniae RP-L7/L12 during in vitro growth and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The anti-RP-L7/L12 mAbs used for manufacturing ICS were prepared by conventional methods described by Sano et al (13). Briefly, RP-L7/L12 was amplified by PCR using genomic DNA from S. aureus (ATCC25923) as template and the following oligonucleotide primers: forward, 5 ′ -CTAGGATCCATGGCTAATCATGAACAAATC-3 ′ , and reverse 5 ′ -CTAGAATTCTTATTTTAATTCTACAGTAGCTCCAAC-3 ′ .…”
Section: Preparation Of Anti-rp-l7/l12 Mabsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-RP-L7/L12 mAbs used for manufacturing ICS were prepared by conventional methods described by Sano et al (13). Briefly, RP-L7/L12 was amplified by PCR using genomic DNA from S. aureus (ATCC25923) as template and the following oligonucleotide primers: forward, 5 ′ -CTAGGATCCATGGCTAATCATGAACAAATC-3 ′ , and reverse 5 ′ -CTAGAATTCTTATTTTAATTCTACAGTAGCTCCAAC-3 ′ .…”
Section: Preparation Of Anti-rp-l7/l12 Mabsmentioning
confidence: 99%
“…Thus, ICS tests are suitable for on-site testing (12). Previous studies have reported the rapid diagnostic usefulness of RP-L7/L12 as a target for the diagnosis of Streptococcus pneumoniae and Mycoplasma pneumoniae infection by ICS tests (13,14). These results have suggested that ICS tests targeting bacterial RP-L7/L12 could be useful for the rapid diagnosis of a variety of infectious diseases, if specific monoclonal antibodies (mAbs) become available for the detection of certain bacterial RP-L7/L12.…”
Section: Introductionmentioning
confidence: 99%
“…Even if an older patient does not meet the JRS criteria, clinicians should investigate a diagnosis of atypical pneumonia when the patient has a persistent cough, which occurred in 88.2% of our older patients with mycoplasma pneumonia (nearly as frequently as in the younger group). A mycoplasma antigen test is now available and might provide a more accurate diagnosis than a mycoplasma antibody test . In addition to the epidemic situation, patient history, physical findings, laboratory findings and radiological findings, and diagnostic tools should be utilized to ensure early treatment, because M. pneumoniae is a difficult pathogen to culture in community clinical settings.…”
Section: Demographic and Clinical Characteristics Of Patients With Mymentioning
confidence: 99%
“…M. pneumoniae IgM has been alternatively used as a diagnostic test at the initial presentation, although there is a 10.1% false positivity rate and a 32.5% false negativity rate with this approach; therefore, testing paired sera of M. pneumoniae IgM is still necessary (Lee et al 2017). Recently, antigen testing for M. pneumoniae has been developed for the rapid detection of M. pneumoniae from nasopharyngeal samples, but the sensitivity is reported to be < 60% (Sano et al 2016).…”
Section: Introductionmentioning
confidence: 99%